Reactive Hyperplasia of the Oral Cavity: A Survey of 197 Cases in Tabriz, Northwest Iran - Amir Ala Aghbali; Sepideh Vosough Hosseini; Bahram Harasi (Tabriz University of Medical Sciences, 2010)
Background and aims. Reactive hyperplastic lesions of the oral connective tissue are associated with injuries of soft tissue and have high prevalence rates and different involvement patterns in different parts of the world. The aim of this study was to analyze demographic data of a university department. Materials and methods. Patient records of the Department of Oral Pathology during a four-year period were reviewed for diagnosis of oral connective tissue reactive hyperplastic lesion. Data including the area involved and the type of lesion were collected and analyzed using descriptive statistical methods and t-test with SPSS 15 statistical software. Results. 197 cases (mean age, 37.68±18.97; male: female ratio, 1.8:1) matched study criterion. The most common affected site was gingiva (83.9%) and the most common lesion was fibroma (45.2%). Giant cell granuloma and pyogenic granuloma were more common in the maxilla than in the mandible. Pyogenic granuloma was seen to be equally distributed in males and females. Conclusion. The results of the present study are overall consistent with the findings of previous studies.